Potential capacity of endoscopic screening for gastric cancer in Japan - Hamashima, Chisato; Goto, Rei (Cancer science, 2017)
In 2016, the Japanese government decided to introduce endoscopic screening for gastric cancer as a national program. To provide endoscopic screening nationwide, we estimated the proportion of increase in the number of endoscopic examinations with the introduction of endoscopic screening, based on a national survey. The total number of endoscopic examinations has increased, particularly in clinics. Based on the national survey, the total number of participants in gastric cancer screening was 3 784 967. If 30% of the participants are switched from radiographic screening to endoscopic screening, approximately 1 million additional endoscopic examinations are needed. In Japan, the participation rates in gastric cancer screening and the number of hospitals and clinics offering upper gastrointestinal endoscopy vary among the 47 prefectures. If the participation rates are high and the numbers of hospitals and clinics are small, the proportion of increase becomes larger. Based on the same assumption, 50% of big cities can provide endoscopic screening with a 5% increase in the total number of endoscopic examinations. However, 16.7% of the medical districts are available for endoscopic screening within a 5% increase in the total number of endoscopic examinations. Despite the Japanese government's decision to introduce endoscopic screening for gastric cancer nationwide, its immediate introduction remains difficult because of insufficient medical resources in rural areas. This implies that endoscopic screening will be initially introduced to big cities. To promote endoscopic screening for gastric cancer nationwide, the disparity of medical resources must first be resolved. Although the Japanese government has decided to introduce endoscopic screening for gastric cancer nationwide, its rapid introduction remains hindered by the insufficient medical resources in rural areas. Thus, endoscopic screening will likely and initially be introduced to big cities. This implies a disparity of medical resources that must be initially resolved to realize a smooth, nationwide implementation of endoscopic screening for gastric cancer.